A Review on Carbon Materials Derived from Biomass Pyrolysis for Supercapacitor Applications - Hamid, Fitri Handayani; Yunita, Kurnia Sri; Mashuni, Mashuni; Jahiding, M; Hasan , Erzam S (Indonesian Journal of Green Chemistry, 2025)
Carbon-based materials are solid carbon enriched with carbon, produced through thermochemical processes such as pyrolysis. However, unmodified and unactivated carbon materials obtained from low-temperature pyrolysis of biomass show poor performance in energy storage applications due to their unsuitable physicochemical and electrical properties, such as low surface area, inadequate pore structure, and low density and conductivity. To improve the properties of carbon, surface modification and activation are applied to enhance carbon's surface features and structure, resulting in better electrochemical performance. Various activation methods are used to modify the surface properties of carbon, making it more suitable for supercapacitor applications. This review provides a comprehensive overview of carbon activation techniques, focusing on their effects on physicochemical and electrical properties and their potential use as supercapacitor electrodes. The article also highlights existing research gaps and suggests directions for future development.